PENGENDALIAN PENYAKIT VIRUS PADA TANAMAN CABAI RAWIT (CAPSICUM FRUTESCENS L.) DENG¬AN MULSA PLASTIK HITAM DAN PERAK - Darmayasa, Dewa Nyoman; Temaja, I Gede Rai Maya; Nyana, I Dewa Nyoman; Suastika, Gede (Journal of Agricultural Science and Biotechnology; Vol 4 No 1 (2015), 2015)
The research of virus diseases management in chili pepper plant ( Capsicum frutescens L.) by utilizing black and silver plastic mulch, was conducted in order to find the capability of black and silver plastic mulch in controlling virus diseases in chili pepper plant and also to find the capability of black and silver mulch in increasing yield of chili pepper plant. This research used randomized block design with 3 treatments and 9 replications. The result of the research shows that utilization of silver plastic mulch had ability to control virus diseases indirectly. The yield of chili pepper has incrising up to 143% with silver plastic mulch treatments.
Keywords: Chili pepper, plastic mulch, virus